A near telomere-to-telomere phased reference assembly for the male mountain gorilla - David R. Nelson; Richard Muvunyi; Khaled M. Hazzouri; Jean-Claude Tumushime; Gaspard Nzayisenga; Nziza Julius; Wim Meert; Latifa Karim; Wouter Coppieters; Katherine M. Munson; DongAhn Yoo; Evan E. Eichler; et al. (Scientific Data)
Abstract The endangered mountain gorilla, Gorilla beringei beringei, faces numerous threats to its survival, highlighting the urgent need for genomic resources to aid conservation efforts. Here, we present a near telomere-to-telomere, haplotype-phased reference genome assembly for a male mountain gorilla generated using PacBio HiFi (26.77× ave. coverage) and Oxford Nanopore Technologies (52.87× ave. coverage) data. The resulting non-scaffolded assembly exhibits exceptional contiguity, with contig N50 of ~95 Mbp for the combined pseudohaplotype (3,540,458,497 bp), 56.5 Mbp (3.1 Gbp) and 51.0 Mbp (3.2 Gbp) for each haplotype, an average QV of 65.15 (error rate = 3.1 × 10−7), and a BUSCO score of 98.4%. These represent substantial improvements over most other available primate genomes. This first high-quality reference genome of the mountain gorilla provides an invaluable resource for future studies on gorilla evolution, adaptation, and conservation, ultimately contributing to the long-term survival of this iconic species.